Activated Carbon From Tamarind Seed And Jackfruit Seed Prepared Via Microwave Irradiated For Dye Removal - Khan, Mohamad Nasran Nasehir (2018)
Water sources such as rivers, lakes, groundwater and seas that located nearby to textile industries can be easily polluted if direct discharge of dye wastewater to the environment is occurred. Adsorbent such as activated carbon particularly produced from agrowaste has been found to be suitable for this purpose. In this study, tamarind seed based activated carbon (TASAC) and jackfruit seed based activated carbon (JASAC) were prepared by using physiochemical activation. It consisted of potassium hydroxide (KOH) impregnation, CO2 gasification and microwave irradiation. A study of batch adsorption for methylene blue (MB) and remazol brilliant blue R (RBBR) were carried out to determine the performance of TASAC and JASAC. Central composite design (CCD) was used to evaluate the optimum preparation conditions of radiation time, radiation power and impregnation ratio (IR) for TASAC and JASAC. The optimum conditions for TASAC were 440 W, 2.0 min and IR 0.5 while for JASAC was 440 W, 2.0 min and IR 0.6, which resulted MB removal of 70.4% and 83.2%, respectively; RBBR removal of 62.7% and 75.6%, respectively and yield of 21.8% and 22.5%, respectively. TASAC and JASAC have high surface area (>869 m2/g), pore volume (> 0.40 cm3/g) and fixed carbon content (>76%). The TASAC and JASAC have heterogeneous type pore size in mesoporous region. The effect of initial dye concentrations (25-300 mg/L), contact times (0-24 hours) and solution temperatures (30-60oC) were determined. The MB and RBBR adsorption by TASAC and JASAC were increased as the initial dye concentration and contact time increased. The adsorption equilibrium data for both dyes onto TASAC and JASAC were best fitted by Freundlich model. Meanwhile, the kinetic data was best represented by the pseudo firstorder kinetic model.